Conceptual Integration of Industry Scenario Cards and Hazard Card in Machining Engineering Learning: A Literature Review On Osh-Oriented Technical Education - Lutfia Santika Dewi; Rubbayyi Shaffiyyah; Khoirun Nikmatul Laili; Adibah Bahrak; Nila Rahmawati (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
Machining engineering learning in higher education faces challenges in balancing technical competency development with occupational safety and health (OSH) awareness. Existing instructional practices in machining workshops are still predominantly product-oriented and procedural, resulting in limited integration of systematic hazard identification and risk analysis during practical activities. This study aims to conceptually examine the integration of industry scenario cards and hazard cards as contextual learning media to support OSH-oriented technical education in machining engineering. This study employed a systematic literature review approach using databases published between 2015 - 2025. The search used keywords including “scenario-based learning”, “hazard card”, “occupational safety and health”, “machining education”, and “engineering education”. The findings indicate that scenario-based learning effectively improves critical thinking, contextual problem solving, and work readiness, while hazard-based visual media strengthen students’ abilities in hazard identification, risk assessment, and safety decision-making. However, previous studies generally implemented both approaches separately and rarely integrated contextual industrial scenarios with systematic workplace hazard analysis in machining education. Therefore, this study proposes a conceptual integration model combining industry scenario cards and hazard cards to support holistic learning involving cognitive, psychomotor, and affective domains. The proposed model contributes theoretically to contextual OSH-oriented vocational pedagogy and practically provides an alternative instructional framework for machining engineering courses in higher education.